TUTOR STRATEGIES IN INCREASING THE MOTIVATION OF STUDENTS TO LEARN AT PKBM BUNDA THROUGH A PARTICIPATORY LEARNING MODEL: STRATEGI TUTOR DALAM MENINGKATKAN MOTIVASI WARGA BELAJAR DI PKBM BUNDA MELALUI MODEL PEMBELAJARAN PARTISIPATIF - Fahman IHLAS NUR FAHMAN; Ady Setiawan; Arif Sugianto; Muhammad Alisalman (SOSIOEDUKASI, 2025)
This study aims to analyze tutor strategies in increasing the motivation of students to learn at PKBM Bunda through the application of a participatory learning model. The research background is based on low motivation to learn, which has an impact on participation, attendance, and the level of equality of the program. This study uses a qualitative approach with a case study design. Data collection techniques were obtained through interviews, observations, and documentation studies. Data analysis techniques include the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that tutors play a role not only as teachers, but also as facilitators, motivators, and learning companions. The strategies implemented include collaborative learning planning, the use of problem-based learning methods, strengthening social interactions, and project-based evaluations that emphasize relevance to the real lives of learning residents. This research complements previous research that generally only highlighted motivation strategies in general and tutor professionalism, This study confirms that the application of participatory learning models in PKBM is effective not only in increasing the intrinsic motivation of learning citizens, but also in strengthening social solidarity and forming a cohesive learning community. These findings prove that the participatory learning model is able to increase intrinsic motivation, active involvement, and confidence of participants, while strengthening social among learning residents.